2016
DOI: 10.1002/2015gl067423
|View full text |Cite
|
Sign up to set email alerts
|

Strike‐slip faulting during the 2014 Bárðarbunga‐Holuhraun dike intrusion, central Iceland

Abstract: Over a 13 day period magma propagated laterally from the subglacial Bárðarbunga volcano in the northern rift zone, Iceland. It created > 30,000 earthquakes at 5–7 km depth along a 48 km path before erupting on 29 August 2014. The seismicity, which tracked the dike propagation, advanced in short bursts at 0.3–4.7 km/h separated by pauses of up to 81 h. During each surge forward, seismicity behind the dike tip dropped. Moment tensor solutions from the leading edge show exclusively left‐lateral strike‐slip faulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
150
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(171 citation statements)
references
References 40 publications
(69 reference statements)
20
150
1
Order By: Relevance
“…We observed a non-uniform spatial distribution of strike-slip and opening mode components, as well as the presence of both left-lateral and right-lateral fault components, among which the former is dominant. Therefore, these results agree with those of seismic (Agustsdottir et al, 2016), geodetic and structural field studies (Ruch et al, 2016). Preexisting topography, earlier fault locations and the locations of eruption sites close to that of an eruption in 1797/98 produced highly variable transtensional displacement with primarily leftlateral strike-slip indicators.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We observed a non-uniform spatial distribution of strike-slip and opening mode components, as well as the presence of both left-lateral and right-lateral fault components, among which the former is dominant. Therefore, these results agree with those of seismic (Agustsdottir et al, 2016), geodetic and structural field studies (Ruch et al, 2016). Preexisting topography, earlier fault locations and the locations of eruption sites close to that of an eruption in 1797/98 produced highly variable transtensional displacement with primarily leftlateral strike-slip indicators.…”
Section: Discussionsupporting
confidence: 81%
“…In transtensional regions located close to the main eruption site, 81% of faults contain left-lateral components, 17% contain right-lateral components, and 2% do not exhibit clear strikeslip components. These results are in agreement with those of independent studies (Agustsdottir et al, 2016), as they reflect the presence of both left-lateral and right-lateral transtensional components at the surface, which Agustsdottir et al (2016) observed at depth.…”
Section: Horizontal Fracture Offsets and Strike-slip Componentsupporting
confidence: 83%
See 2 more Smart Citations
“…Our rates are slightly lower than the rates observed elsewhere 15;28 30 and are non-steady state. These interpretations nd further support in the following observations: (i) most dyke related seismicity was in the 5 to 8 km depth range according to results from the IMO permanent network 10 and a temporary, more dense network 15 . However, shallowing seismicity at less than 5 km depth was observed around C1 and C2 before August 27 th ( gure 1 and 15 ).…”
Section: Tremor Marks Shallow Dyke Formationsupporting
confidence: 69%